El ejercicio de inculturación de la espiritualidad: aporte de Gustavo Gutiérrez en “Beber en su propio pozo” (2018)
This paper seeks to give an account of the inculturation character of spirituality that is present in the work: “Drinking from your own well”, evidencing the appropriation of the elements of culture through which the action of the Spirit was expressed in the ecclesial communities existing in Latin America. This contribution can be a source of inspiration to account for the multiple manifestations of the Spirit that can be forged within society and be an important reference to the need to inculturate both theology and spirituality today.